MOTHER'S KNOWLEDGE AND HYGIENE SANITATION AGAINST STUNTING IN TODDLERS - Agus Darmawan; Nur Rahmy Basry; Wahyuddin Wahyuddin (Jurnal Riset Kesehatan, 2022)
Toddler development can be disrupted if there are nutritional problems such as stunting. One of the factors that influence stunting is knowledge about nutrition and sanitation hygiene. Knowledge of maternal nutrition will affect children's food intake, while hygiene behavior is related to the incidence of infection in children. This study aims to determine the relationship between the incidence of stunting in children under five and mothers’ knowledge about nutrition and sanitation. This type of study was analytic observational with a cross-sectional study design. The number of samples in this study was 90 people in two villages (Laburunci and Dongkala villages, Pasarwajo sub-district, and Buton district). Sampling used the Non-Probability Sampling technique. The variable incidence of stunting was the dependent variable of this researcher, while the independent variable consisted of the mother's knowledge and sanitation hygiene. Univariate and bivariate data analysis with a chi-square test was carried out in this study. There was a relationship between the mother’s knowledge (p=0.000) and sanitation hygiene (p=0.000) of the incidence of stunting in the working area of the Banabungi Public Health Center. This study concluded that to prevent the toddler from stunting we need to increase the mother’s knowledge against stunting and efforts to improve sanitation hygiene to minimize the risk of infection which can affect the nutritional status of toddlers. Therefore, this study should be a base for the government to provide socialization about nutrition and hygiene sanitation to the community so that it can be applied in daily life.